2017
DOI: 10.17508/cjfst.2017.9.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Levels of selected metals in wines from different Herzegovinian viticultural localities

Abstract: SummaryConcentrations of seven metals indicated as hazardous to human health (Pb, Cu, Zn, Mn, Ni, V, and Cr) were determined in 24 Hezegovinian white and red wines originating from four viticultural localities (Čitluk, Ljubuški, Stolac, and Trebinje). The concentrations of Pb, Cu, Mn, Ni, V, and Cr were determined by the ET AAS, and Zn concentrations were determined by the FAAS technique. Among seven measured metals, Zn and Mn were found in all analysed wines, while Ni was found in only four, and Cr in only fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Metals enter a wine as a final product in different ways, while their structure and concentration in wine depend on at least four sources. The first, and frequently mentioned source, involves soil on which a vineyard area is established, and capacity of wine to absorb various mineral sustances (Blesić et al, 2017). The second source is linked to the ways and conditions of grape production, among which applications of pesticides and environmental air pollution are frequently stressed (Angelova et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals enter a wine as a final product in different ways, while their structure and concentration in wine depend on at least four sources. The first, and frequently mentioned source, involves soil on which a vineyard area is established, and capacity of wine to absorb various mineral sustances (Blesić et al, 2017). The second source is linked to the ways and conditions of grape production, among which applications of pesticides and environmental air pollution are frequently stressed (Angelova et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Metals in wines may have a number of roles, organoleptic characteristics can be influenced positively or negatively, through causes of theier different instabilities, to the fact that wines can be considered sources of metals needed in human diet (Blesić et al, 2017). Besides the metals which are typically abundant in grapes (Ca, Mg and K), metals such as Cu, Fe, Cr, Zn and Mn are necessary or useful in a series of physiological processes in wine yeasts and humas (Marais and Blakhurst, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The authors affirm that several factors may contribute to these different concentrations, such as vine cultivation, the winemaker's knowledge, storage, fertilizers and fungicides. Blesic et al [30] determined Zn in merlot wine from different locations by AAS and the concentrations quantified were 526 and 1856 µg L −1 showing that the location influences the Zn concentration in the samples from the same grape variety and the same vintage (2010).…”
Section: Resultsmentioning
confidence: 99%
“…Bentlin et al [29] quantified Pb in wine from 0.6 to 26 µg L −1 (samples from Brazil), from 2 to 53 µg L −1 (samples from Argentina), from 2.5 to 28 µg L −1 (samples from Chile) and from 8 to 82 µg L −1 (samples from Uruguay). Blesic et al [30] determined Pb by spectrometry and found 30 and 47 µg L −1 in Merlot (2010) cultivated in different places. Dessuy et al [33] developed a method for Pb determination in wine by spectrometry without any sample preparation and the results obtained for seven samples using the proposed method as well as the analyses after an acid digestion procedure did not show any significant difference (using a Student's t-test).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation